Preserved Autonomic Cardiovascular Regulation With Cardiac Pacemaker Inhibition: A Crossover Trial Using High‐Fidelity Cardiovascular Phenotyping. Issue 1 (January 2016) - Heusser, Karsten; Tank, Jens; Brinkmann, Julia; Schroeder, Christoph; May, Marcus; Großhennig, Anika; Wenzel, Daniela; Diedrich, André; Sweep, Fred C. G. J.; Mehling, Heidrun; Luft, Friedrich C.; Jordan, Jens
Abstract : Background: Sympathetic and parasympathetic influences on heart rate (HR), which are governed by baroreflex mechanisms, are integrated at the cardiac sinus node through hyperpolarization‐activated cyclic nucleotide–gated channels (HCN4). We hypothesized that HCN4 blockade with ivabradine selectively attenuates HR and baroreflex HR regulation, leaving baroreflex control of muscle sympathetic nerve activity intact. Methods and Results: We treated 21 healthy men with 2×7.5 mg ivabradine or placebo in a randomized crossover fashion. We recorded electrocardiogram, blood pressure, and muscle sympathetic nerve activity at rest and during pharmacological baroreflex testing. Ivabradine reduced normalized HR from 65.9±8.1 to 58.4±6.2 beats per minute ( P <0.001) with unaffected blood pressure and muscle sympathetic nerve activity. On ivabradine, cardiac and sympathetic baroreflex gains and blood pressure responses to vasoactive drugs were unchanged. Ivabradine aggravated bradycardia during baroreflex loading. Conclusions: HCN4 blockade with ivabradine reduced HR, leaving physiological regulation of HR and muscle sympathetic nerve activity as well as baroreflex blood pressure buffering intact. Ivabradine could aggravate bradycardia during parasympathetic activation. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00865917.